An Effective and Practical Tool for Conveying Test Deck Concepts. - McKeown, James C. (The Accounting Review, 1973)
Abstract The article focuses on an assignment developed to teach accounting students the use of test decks in verifying the performance of an operating data processing system. The assignment was developed in a manner which minimizes both class time and student time required to give the students a clearer understanding of the use of test decks and their limitations. Only one additional class hour was required. Since most of the additional class time is spent orienting the students to a realistic computer accounting program, the time spent should not be considered as solely aiding the test deck presentation in that the instructor can later use the students' exposure to a typical computer application as a basis in discussion of further computer-related topics and/or contrast with similar manual systems. The program used to process the student test decks actually simulates a payroll program. Since many parameters which affect payroll processing change frequently, most of them are read by the program as data at the beginning of each run. The program will process a batch of up to 200 student decks in one run.